Enhancement in the Specific Energy of B‐doped Graphene Using Redox Additive Electrolytes. Issue 31 (20th August 2020) - Suresh Balaji, S.; Mohammad Tauquir, Shaikh; Karnan, M.; Moorthy, Megala; Sathish, M.
Abstract: Electrochemical performance of carbon materials can be enhanced by doping with heteroatoms. Electrochemical investigations suggest that the B‐doped graphene in which B‐source and graphene oxide are in the ratio 1 : 1 demonstrates a highest specific capacitance of 406 F/g at 2 A/g in 1 M H2 SO4 . The specific capacity of B‐doped graphene in 0.01 M hydroquinone (HQ)/H2 SO4 is 2523 C/g in redox additive electrolyte. Performance evaluation of fabricated symmetric supercapacitor cell indicates that the specific capacitance in 0.01 M HQ/H2 SO4 and 1 M H2 SO4 solution are found to be 440 and 284 F/g at 3 A/g, respectively and greater than EMIMBF4 (97 F/g). The maximum specific energy of the fabricated symmetric cell achieved using 0.01 M HQ/H2 SO4 solution is found to be 50 Wh/kg which is comparatively superior than 1 M H2 SO4 (14.2 Wh/kg) and EMIMBF4 (30 Wh/kg). Abstract : B‐doped graphene was prepared via supercritical fluid route using sodium borohydride as a boron source. The specific capacity of B‐doped graphene in 0.01 M hydroquinone (HQ)/H2 SO4 is 2523 C/g in redox additive electrolyte because it exhibits a battery type behaviour in redox additive electrolyte. The full cell studies in various electrolytes revealed that a specific energy of 50 Wh/kg was obtained in 0.01 M HQ/H2 SO4 which is comparatively superior than 1 M H2 SO4 (14.2 Wh/kg) and EMIMBF4 (30 Wh/kg).